Pemanfaatan Limbah Teh sebagai Alternatif PemeliharaanKesehatan Gigi dan Mulut yang Ramah Lingkungan di Sekolah Lansia Sukmajaya Bahagia - Ranggaini, Dewi; Astuti, Luki; Ihsan Rizal, Muhammad; Trisfilha, Pretty; Halim, Johni; Nova Fitri, Andrian (Fakultas Kedokteran Gigi, Universitas Trisakti bekerjasama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2025)
Oral health among the elderly is often neglected, while chemical-based oral care products may pose potential risks to health and the environment. Tea waste, which is usually discarded, contains antibacterial properties that can help maintain oral hygiene. This program aimed to educate the elderly about the benefits of tea waste and provide training on its utilization as an environmentally friendly alternative for oral health care. The activity employed counseling and hands-on training, targeting 50 elderly participants at Sekolah Lansia Mekarjaya Bahagia, Depok, West Java, on July 12, 2025. The session included material on tooth structure, causes and prevention of dental caries, periodontal tissue damage, oral care practices (proper tooth brushing and dental flossing), and the benefits of natural materials, particularly tea waste. The program continued with practical training in making a mouthwash using tea waste as a sustainable oral care option. The activity was successfully conducted with high participant engagement. Evaluation results showed an increase in knowledge and positive attitudes toward oral health maintenance and the use of tea waste as a mouthwash before and after the training. In conclusion, this program effectively improved awareness among the elderly regarding natural and eco-friendly oral care practices. It is recommended to continue structured community engagement and utilize social media platforms to reach a wider audience.